2022
DOI: 10.1002/pbc.29625
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of clinical and radiological predictors of retinoblastoma with high‐risk histopathological features

Abstract: Introduction: Retinoblastoma (RB) tumors having high-risk histopathologic features (HRFs) have an increased risk of metastasis and disease relapse. However, RB has not been studied widely in Pakistan. Therefore, we evaluated the association of clinical, histopathologic, and radiological findings with HRFs in patients with RB who were

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Factors that may affect eye preservation include eye‐preserving therapy, IIRC groups and various clinical risk factors, such as retinal detachment, corneal edema, anterior chamber haemorrhage and iris neovascularization. (Yaqoob et al, 2022) With growing experience and an increasing number of treatments, several complications have been reported. Retinoblastoma rarely presents with vitreous haemorrhage, and conversely, degradation of vitreous haemorrhage due to any cause can be misdiagnosed as retinoblastoma in a minority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that may affect eye preservation include eye‐preserving therapy, IIRC groups and various clinical risk factors, such as retinal detachment, corneal edema, anterior chamber haemorrhage and iris neovascularization. (Yaqoob et al, 2022) With growing experience and an increasing number of treatments, several complications have been reported. Retinoblastoma rarely presents with vitreous haemorrhage, and conversely, degradation of vitreous haemorrhage due to any cause can be misdiagnosed as retinoblastoma in a minority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Yaqoob et al found that among 54 patients, the main histopathological traits included choroidal invasion, observed in 18 patients, along with the anterior invasion of the optic nerve anterior to the lamina cribrosa, observed in 16 patients. Through association analysis, the researchers also found that clinical features such as pseudohypopyon, iris neovascularization, buphthalmos, and glaucoma were associated with choroidal infiltration [ 110 ]. Additionally, Kashyap et al also highlighted correlations between features such as glaucoma and iris neovascularization and the incidence of high-risk histopathological findings [ 111 ].…”
Section: Pathology Of Rbmentioning
confidence: 99%